Gender, work, and harness racing : fast horses and strong women in southwestern Pennsylvania - Larsen, Elizabeth Anne, 1968- (Lexington Books, 2014)
Elizabeth Anne Larsen explores how harness horse racing has resisted gender equalization and excluded women from key roles. With stirring accounts of the strong women who are surviving and succeeding in this sport, Larsen provides insight for studies of gender and work, occupational sex segregation, and women's studies.